2022
DOI: 10.3389/fonc.2022.880336
|View full text |Cite
|
Sign up to set email alerts
|

MRI/Transrectal Ultrasound Fusion-Guided Targeted Biopsy and Transrectal Ultrasound-Guided Systematic Biopsy for Diagnosis of Prostate Cancer: A Systematic Review and Meta-analysis

Abstract: PurposeFor men suspected of having prostate cancer (PCa), the transrectal ultrasound (TRUS)-guided systematic biopsy (SB) was performed. MRI/TRUS fusion guided-targeted biopsy (MRI-TB) could enhance PCa detection, allowing sampling of sites at higher risk which were not obvious with TRUS alone. The aim of this systematic review and meta-analysis was to compare the detection rates of prostate cancer by MRI-TB or MRI-TB plus SB versus SB, mainly for diagnosis of high-risk PCa.MethodsA literature Search was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
1
11
0
2
Order By: Relevance
“…The advancement in prostate cancer diagnosis has developed MRI-TRUS fusion-guided needle biopsies to efficiently predict prostate cancer [ 49 , 50 ]. The technique is time-consuming and laborious, so AI has been introduced to automate the process to reduce the burden on clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…The advancement in prostate cancer diagnosis has developed MRI-TRUS fusion-guided needle biopsies to efficiently predict prostate cancer [ 49 , 50 ]. The technique is time-consuming and laborious, so AI has been introduced to automate the process to reduce the burden on clinicians.…”
Section: Resultsmentioning
confidence: 99%
“…Проведение МР-прицельной биопсии, предположительно, снижает выявление клинически незначимых форм РПЖ. При выполнении мпМР/УЗ fusion-биопсии выявляемость клинически незначимого РПЖ меньше по сравнению со стандартной биопсией, что подтверждается данными исследований MRI-FIRST (5,6 и 19,5 %; p <0,001) и 4M (14 и 25 %; p <0,001) [14,20], а также метаанализа, в котором показано, что выявляемость клинически незначимого РПЖ ниже при выполнении МР-прицельной биопсии по сравнению со стандартной (относительный риск 0,65; 95 % доверительный интервал 0,55-0,77; p <0,001) [23]. Тем не менее результаты нашей работы не подтверждают это предположение, что, в свою очередь, согласуется с данными, полученными H. Goldberg и соавт.…”
Section: Discussionunclassified
“…В ряде работ отмечается более высокая общая выявляемость РПЖ при проведении мпМР/УЗ fusion-биопсии, чем при стандартной биопсии [23,25]. Однако при сравнении общей выявляемости РПЖ в исследовании M. Kroenig и соавт.…”
Section: Discussionunclassified
“…Meanwhile, mpMRI-TRUS fusion imaging has been advocated for clinical application. Xie [ 17 ] analyzed the literature on mpMRI-TRUS fusion imaging from 2012 to 2021 and showed that the fusion imaging-guided TB had a higher detection rate of csPCa. Similarly, we confirmed that TB was higher than SB for detecting csPCa (p < 0.05) but our results included the TB guided by mpUS.…”
Section: Discussionmentioning
confidence: 99%